Research methods for organizational studies - Schwab, Donald P. (L. Erlbaum Associates, 2005)
This revision of a best selling research methods textbook introduces social science methods as applied broadly to the study of issues that arise as part of organizational life. These include issues involving organizational participants such as managers, teachers, customers, patients and clients, and transactions within and between organizations. In this new edition, chapter 19 now focuses on describing the modeling process and outcomes. An entirely new chapter 20 now addresses challenges to modeling. It goes substantially beyond a discussion of statistical inference. It also discusses.